(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
Thispaper discusses therelationshipbetween understanding andbeingatthe one of most importantexistentialistphilosophers, aGerman philosopherHeidegger. Based onthe study ofthis relationshipand interpretedin his philosophy, In an attempt toidentifya wayto achievetheirbeingWhich isthe existence ofassets, and show the meaning of dasein and being,In addition tointerpret the meaning ofhuman existence and its importancebecause he is theonly one who canask a questionof existence. in an attempt toidentifythe elements ofthis existence andunderstanding ofwhichrepresentsone of them, in order to distinguish betweenauthenticexistenceand pseudo-existence,and clarify an experience anxiety and it’s importanceand the necessary mechanisms to get to authentic existence, through a series ofanalyzes of thenotions ofunderstanding andbeingin Heidegger philosophy, In an attemptto analyze the moments of existence which are: (World)– (existin the world) –(presence in the world)